2021
DOI: 10.1186/s12951-021-00923-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals the mechanism of sonodynamic therapy combined with a RAS inhibitor in the setting of hepatocellular carcinoma

Abstract: Background Ras activation is a frequent event in hepatocellular carcinoma (HCC). Combining a RAS inhibitor with traditional clinical therapeutics might be hampered by a variety of side effects, thus hindering further clinical translation. Herein, we report on integrating an IR820 nanocapsule-augmented sonodynamic therapy (SDT) with the RAS inhibitor farnesyl-thiosalicylic acid (FTS). Using cellular and tumor models, we demonstrate that combined nanocapsule-augmented SDT with FTS induces an anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…As reported in previous studies, we have prepared RSL3@O 2 -ICG NBs using the thin-film hydration ultrasound method. 44 First, mix DSPC and DSPE-PEG-2000 at a mass ratio of 9:1, and then add 10ul of 5 mM RSL3 in methylene chloride and methanol (2:1, vol/vol). After entirely dissolving and mixing, transfer the above solution to a beaker and evaporate to form a lipid film.…”
Section: Methodsmentioning
confidence: 99%
“…As reported in previous studies, we have prepared RSL3@O 2 -ICG NBs using the thin-film hydration ultrasound method. 44 First, mix DSPC and DSPE-PEG-2000 at a mass ratio of 9:1, and then add 10ul of 5 mM RSL3 in methylene chloride and methanol (2:1, vol/vol). After entirely dissolving and mixing, transfer the above solution to a beaker and evaporate to form a lipid film.…”
Section: Methodsmentioning
confidence: 99%
“…Identifying new combinations helps tremendously with immunotherapy strategies where most patients do not respond to monotherapy as a first-line treatment [45]. In a recent study, single-cell RNA sequencing was performed to show that a combinational strategy using both an RAS inhibitor and IR820 nanocapsuleaugmented sonodynamic therapy suppressed hepatocellular carcinoma and modulated immunity through differentially expressed genes [46]. In a similar study, single-cell sequencing was performed on CD45 + tumor-infiltrating lymphocytes (untreated controls or PDL1 and AB680 CD73 inhibitor treated) to find that CD73 inhibition is distinct from PDL1 inhibition [47].…”
Section: Translational Relevance Of Single-cell Sequencing Technologiesmentioning
confidence: 99%
“…Multiple studies have supported that multifunctional sonosensitizers could alter gene expression in cancer and immune-related cells and revealed therapeutic target genes in various signaling pathways by the data analysis. [158][159][160][161] For example, Wu et al designed IR820@NCP using RAS inhibitor Farnesyl-Thiosalicylic acid (FTS) to demonstrate that SDT combined with FTS predominantly achieved anti-tumour effects by inhibiting endothelial cells and simulating host immunity. 160 In Chen et al's research on the treatment of liver cancer by RSL3@O2-ICG NBs, essential genes were identified to affect the sensitivity of hepatocellular carcinoma to iron death.…”
Section: Sonosensitizers Beyond Imagingmentioning
confidence: 99%
“…[158][159][160][161] For example, Wu et al designed IR820@NCP using RAS inhibitor Farnesyl-Thiosalicylic acid (FTS) to demonstrate that SDT combined with FTS predominantly achieved anti-tumour effects by inhibiting endothelial cells and simulating host immunity. 160 In Chen et al's research on the treatment of liver cancer by RSL3@O2-ICG NBs, essential genes were identified to affect the sensitivity of hepatocellular carcinoma to iron death. 158 In addition to molecular imaging techniques, such gene and protein level monitoring could be achieved by reporter imaging techniques that combined reporter proteins with corresponding imaging probes.…”
Section: Sonosensitizers Beyond Imagingmentioning
confidence: 99%